Desempenho agronômico de genótipos de cana-de-açúcar no Estado do Rio Grande do Sul - Veríssimo, Mario Alvaro Aloisio (2012)
Brazil is the world leader in the production of sugarcane. This crop is of great importance to Brazil and to Rio Grande do Sul State, where the family farming has the largest area planted with sugarcane. There is increasing demand for technical information about the sugarcane cultivation in this State, with the aim at ethanol production. Genotype x environment interaction is one of the main factors to be evaluated in the development of the production systems. The objective of this research was to evaluate the agronomic performance of sugarcane genotypes in different environments of the Rio Grande do Sul State. The characters tons of stalks per hectare (TCH), tons of Brix per hectare (TBH), maturation, disease occurrence and cold tolerance of sugarcane genotypes were evaluated. Adaptability and stability was evaluated by methodology AMMI (Additive Main Effects and Multiplicative Interaction), based on the variables TBH and TCH. The results indicate that the genotype x environment interaction is significant, with genotypes broadly adapted and stable, as well as behavior specific genotypes to particular environments. Diseases such as brown rust, smut, leaf scald and red stripe incidence and striations were regionalized. The brown spot (Cercospora longipes) showed wide occurrence with high severity for some genotypes in certain environments. Regarding the cold tolerance, the genotypes showed different degrees of tolerance. The set of early maturity genotypes RB966928, RB925345, RB855156, RB975935, RB975944 and RB996961, and mid-late maturity RB987932, RB987935, RB935744 and RB008347 have good agronomic performance, which combined properly can be part of a system of sugarcane production to Rio Grande do Sul.